1995
DOI: 10.1159/000113259
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental Learning in Toads (<i>Bufo arenarum</i>):Reinforcer Magnitude and the Medial Pallium

Abstract: Two experiments studied the effects of shifts in the amount of water reinforcement on the instrumental performance of toads (Bufo arenarum) using one trial per day. In the first experiment, a shift from a large to a small reward magnitude led to a gradual change in performance without evidence of negative contrast. A shift from large or small reward magnitude to extinction led to similar extinction rates and provided no indication of the magnitude of reinforcement extinction effect. In the second experiment, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 16 publications
6
43
0
Order By: Relevance
“…The pigeon's operant performance after the shift was directly related to the magnitude of reinforcement before the shift and not inversely related as predicted by frustration theory (Amsel, 1992). This is not an uncommon outcome in analogous experiments with lower vertebrates, but it is a different pattern of results from that typically obtained with mammalian species (Papini, Muzio, & Segura, 1995).…”
Section: Discussionmentioning
confidence: 55%
“…The pigeon's operant performance after the shift was directly related to the magnitude of reinforcement before the shift and not inversely related as predicted by frustration theory (Amsel, 1992). This is not an uncommon outcome in analogous experiments with lower vertebrates, but it is a different pattern of results from that typically obtained with mammalian species (Papini, Muzio, & Segura, 1995).…”
Section: Discussionmentioning
confidence: 55%
“…Available evidence from spaced-trial experiments with osteichthyes fish, amphibians, and reptiles indicates that only the allocentric effects of SN are present in these animals [see Papini et al, 1995;Bitterman, 2000]. Thus, for example, a shift from a large to a small reward magnitude is followed by an adjustment of performance without deterioration, that is, without SNC.…”
Section: Surprising Nonreward In Fish Amphibians and Reptilesmentioning
confidence: 99%
“…11; see vOB y LS y vMP Y A Y R) [Hoffmann, 1973;Kicliter and Northcutt, 1975;Northcutt and Royce, 1975;Northcutt and Kicliter, 1980;Neary and Wilczynski, 1980]. Previous 14 C-2DG studies have shown that activity in the ventral medial pallium is associated with conditioning [see Finkenstädt, 1989;Finkenstädt et al, 1985;Merkel-Harff and Ewert, 1991;Papini et al, 1995;Ewert et al, 1994bEwert et al, , 1999. The increase in glucose utilization in the ventral medial pallium might also result from the action of APO as a positive reinforcer [e.g.…”
Section: Apo-induced Facilitation Of Snappingmentioning
confidence: 99%